Biodiesel Production from Acidified Oils via Supercritical Methanol - Jianxin Li; Benqiao He; Jincheng Ding (Energies, 2011)
In biodiesel production, the vegetable oil used as raw material for transesterification should be free of water and free fatty acids (FFAs), which may consume catalyst and reduce catalyst efficiency. In this work biodiesel was prepared from acidified oils (AO) through a supercritical methanol route, in which the esterification of FFAs and transesterification of glyceride with methanol occurred simultaneously. The effects of the mass ratio of methanol to AO, the operation temperature as well as the water content on the FFAs conversion and glycerol yield were investigated. The results indicated that the FFAs conversion for esterification under the condition of 1:1 methanol/oil ratio, 310 °C and 15 min reaction time reached 98.7%, and the glycerol yield for transesterification under 0.25:1 methanol/oil ratio, 290 °C and 20 min reaction time reached 63.5% respectively.